Near-surface ocean temperature and air-sea heat flux observed by a buoy array during summer to autumn in year 2014 in the northern South China Sea - Wu, Zixi; Zhang, Han (Frontiers in Marine Science, 2024)
The observational data of the air-sea interface and upper ocean elements from a buoy array deployed in the northern South China Sea from June to November 2014 is analyzed. The COARE 3.0 algorithm was adopted to compute the heat exchange between ocean and atmosphere, including during two typhoon events. The temporal variations in near-surface ocean temperature and air-sea heat flux, and their relationships with air-sea interface conditions were analyzed. In addition, the contributions of air-sea heat fluxes during different periods within the observation time period to the changes in near-surface ocean temperature were analyzed. During the observation period, the sea surface temperature slowly decreasing with the seasons, averaging 28.1℃ in summer and 27.5°C in autumn. After the transition to winter monsoon, the sea surface temperature showed an overall cooling trend, with a pronounced seasonal cooling, averaging 28.4℃ in summer and 27.9°C in winter.During summer monsoon, the differences in the air-sea heat fluxes measured at stations 2 and 4 were relatively large, which may be influenced by other weather processes. During the monsoon transition period, the contribution of air-sea heat flux to the recovery of sea surface temperature is relatively large. The water column mixing became more uniform, and the temperature difference between the upper and lower layers gradually decreased, leading to a gradual temperature decline. The contribution of air-sea heat flux to the decrease in near-surface ocean temperature during winter monsoon is greater than 60%. Following the passage of a typhoon, the maximum sea surface cooling reached 3.4°C, with significant decrease in the near-surface ocean temperature. Under typhoon conditions, the air-sea heat fluxes had a relatively small impact on the changes in near-surface ocean temperature. The air-sea heat flux exchange in the northern South China Sea is primarily determined by the combined effects of solar shortwave radiation and latent heat flux. The net heat flux is mostly negative, indicating that the ocean predominantly loses heat. During the typhoon period, the net airsea heat flux was significantly suppressed, mainly due to a reduction in solar shortwave radiation, while the contribution of sensible heat flux was minimal.